Plasma D-dimer and Prothrombin Fragment 1+2 in Evaluating the Occurrence of Venous Thromboembolism in Advanced Cancer Patients and the Effect of Preventive Anticoagulant Therapy: D-dimer and Prothrombin Fragment 1+2 in Evaluating the Occurrence of Venous Thromboembolism - Fu, Huiying (Journal of Medical Biochemistry, 2025)
Introduction: This article aimed to investigate the value of D-dimer (DD) and prothrombin fragment 1+2 (PF1+2) in evaluating the risk of venous thromboembolism (VTE) in advanced cancer patients and the effect of preventive anticoagulant therapy. Method and Material: 137 advanced cancer patients who were hospitalized in The 908th Hospital of Chinese People’s Liberation Army Joint Logistic Support Force Hospital from February 2023 to June 2024 were recruited. They were divided into VTE group (n=49) and non-VTE group (n=88) according to whether VTE occurred. Blood routine test was performed on admission, and the relationship between DD and PF1+2 and VTE was analyzed. The role of DD and PF1+2 as risk assessment indicators for VTE was evaluated. The subjects without VTE were divided into preventive anticoagulant treatment group (AG, n=48) and conventional anticoagulant treatment group (RT, n=40) according to their will. The probability of VTE in the two groups after treatment was counted to verify the effect of preventive anticoagulant intervention. Result: Before chemotherapy for advanced cancer, DD was higher in the subjects with VTE as against subjects without VTE. DD and PF1+2 after chemotherapy are independent risk factors for VTE. The effect of VTET was different, while other treatments had no distinction. The incidence of VTE in RT group was higher as against AG group, the distinction had statistical meaning. Conclusion: DD and PF1+2 can be used as indicators to evaluate the risk of VTE in advanced
Keywords: DD; PF1 2; Advanced cancer patients; VTE; Value assessment